The impact of leadership competency, organizational culture, job satisfaction, and employee performance in public administration - Harry Yanza Putra; Okka Adittio Putra (Privietlab, 2024)
This study examines the impact of leadership competency, organizational culture, and job satisfaction on employee performance in the public administration sector in Bengkulu. Using a quantitative approach, data were collected from 113 leaders in public institutions. The research model, consisting of four variables and five hypotheses, was tested using Structural Equation Modeling (SEM) with AMOS software. The findings reveal significant relationships among leadership competency, organizational culture, job satisfaction, and employee performance. The study contributes to public administration and human resource management by providing insights into how leadership and organizational factors influence employee performance in a government setting. The results offer practical implications for policymakers and administrators in enhancing leadership development and fostering a positive work environment to improve public sector performance.